Effect of Light Spectrum LED Lettuce on IoT-Based Indoor Farming - Moh. Haris Imron S Jaya; Septafiansyah Dwi Putra; Imam Sofi'i (Universitas Brawijaya, 2023)
Lettuce (Lactuca sativa L.) is an economically important crop worldwide and one of the most popular species grown in indoor farming. Lettuce's fast growth and cycle make a model plant to study the interaction between plants and light. Light's influence is one of the fundamental environmental factors for plant growth and development. Light-emitting diodes (LEDs) have higher light efficiency and wear efficacy, leading to a reduction in associated heating compared to other artificial lighting sources, such as fluorescent lamps or sodium vapor lamps. This research aimed to determine the morphological response of lettuce by giving an LED light spectrum with a single colour spectrum and IOT-based temperature and humidity monitoring. This research used a students’ t-test with a level of 5% on the mean value of the white light spectrum with a yellow light on lettuce plants. Adding LED light spectrum produces a different response to the morphological parameters. LED spectrum affected the plant height variable, where the provision of a yellow LED light spectrum increased the plant height of lettuce.